2013
DOI: 10.1038/ncomms2500
|View full text |Cite
|
Sign up to set email alerts
|

Holographic optogenetic stimulation of patterned neuronal activity for vision restoration

Abstract: When natural photoreception is disrupted, as in outer-retinal degenerative diseases, artificial stimulation of surviving nerve cells offers a potential strategy for bypassing compromised neural circuits. Recently, light-sensitive proteins that photosensitize quiescent neurons have generated unprecedented opportunities for optogenetic neuronal control, inspiring early development of optical retinal prostheses. Selectively exciting large neural populations are essential for eliciting meaningful perceptions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 45 publications
1
97
0
1
Order By: Relevance
“…This figure goes beyond Proposition 4 by suggesting that the magnitude of steady-state oscillations can be arbitrarily reduced by uniform proportional feedback, provided that a sufficiently large gain k is used. This observation is encouraging from a implementation viewpoint as, despite the development of holographic techniques (Reutsky-Gefen et al, 2013), uniform photostimulation remains more realistic.…”
Section: Parameters Choicementioning
confidence: 83%
See 1 more Smart Citation
“…This figure goes beyond Proposition 4 by suggesting that the magnitude of steady-state oscillations can be arbitrarily reduced by uniform proportional feedback, provided that a sufficiently large gain k is used. This observation is encouraging from a implementation viewpoint as, despite the development of holographic techniques (Reutsky-Gefen et al, 2013), uniform photostimulation remains more realistic.…”
Section: Parameters Choicementioning
confidence: 83%
“…Moreover, the control signal (4) depends on r: it thus requires to deliver a stimulation that may differ from one position to another. Despite progresses in holographic techniques (Reutsky-Gefen et al, 2013), this may be hard to achieve in practice. A more realistic strategy would be to rely on the averaged activity of the controlled population:…”
Section: Proposed Feedback Lawsmentioning
confidence: 98%
“…Optogenetics was studied for the application of vision restoration, 43 and a recent study demonstrated the use of a holographic system for patterned light stimulation of mice retina with millisecond temporal precision and cellular resolution. 55 Generating photoactivitated neurons in specific parts of brains of freely moving animals was studied as a means to achieve controlled behavioral response. 56 Illumination of genetically modified neurons in drosophila flies resulted in complex behaviors, such as jumping, wing beating, and flight, specific to the functionality of the brain area where neuronal modification was performed.…”
Section: Optogeneticsmentioning
confidence: 99%
“…has mainly been used in conjunction with two-photon stimulation for the excitation of neurons in deep tissue, like mouse brains, but mostly using SLMs with only tens of frames per second [30,31]. Also, fast ferroelectric SLMs were used in the past for the stimulation of blinded mouse retinas [32], albeit using the inherent modulation speed only for speckle reduction with shift-averaged holograms. A review of optical techniques for optogenetics can be found in [24].…”
Section: Holographic Single-cell Illumination Setupmentioning
confidence: 99%
“…Usage of the FSLM was reported previously [32]. There, a Fourier hologram scheme was employed to steer a focus over mouse retinas.…”
Section: Computer-generated Hologramsmentioning
confidence: 99%